El destino del Inca Garcilaso en el cuento hispanoamericano (Altre Modernità, 2018)
This article recreates the figure of the historical Inca Garcilaso de la Vega as a fictional character. In its first part, the paper exposes the importance of the humanist writer as introducer of the literary tale in Spanish-American literature. Thus, the concept of "fabula historial" is presented by him in his "Comentarios reales". The second part of the article explores the presence of the Inca Garcilaso de la Vega as character in a tale by the Argentine writer Manuel Mujica Láinez.